Identification of Factors Causing Student Athlete Burnout of SMA Negeri 15 Surabaya - Dygra Irdyandiwa; Nanik Indahwati; Anung Priambodo (UNIVERSITAS NEGERI MAKASSAR, 2023)
Learning is a process of interaction between students and educators and learning resources in a learning environment. PJOK is a place to determine and look for talent in students. Students can determine which sports are mastered. This study used a questionnaire instrument which was then processed using Structural Equation Modeling (SEM). This study aims to determine the factors that cause burnout and which factors are most dominant in student-athletes at SMA Negeri 15 Surabaya. The research sample was made to fulfil the thesis namely student-athletes at SMA Negeri 15 Surabaya as many as 66 respondents using multiple linear regression analysis. Based on the results of analysis and research conducted, social support does not affect burnout, motivation has a significant effect on burnout, reward does not affect burnout, and fatigue has a significant effect on burnout. Based on the results of the F test of social support, motivation, and rewards. and fatigue simultaneously has a significant effect on burnout. Based on the results of the regression test of social support, motivation, and reward. and fatigue to burnout. Motivation has a regression coefficient value that stays away from the number 0, this means that the variables that have the most dominant influence are social support, motivation, and rewards. and burnout are motivational variables.